Evaluación otorrinolaringológica para decanulación y de la deglución en el paciente traqueostomizado no-neurocrítico en cuidados intensivos - Alvo V., Andrés; Olavarría L., Christian (Revista Hospital Clínico Universidad de Chile, 2013)
On intensive care patients, decannulation and deglutition disorders are frequent reasons for otorhinolaryngologic assessment. The objective of a tracheostomy is to maintain a patent airway. It does not necessarily prevent episodes of aspiration and may even favor them. When the condition leading to the tracheostomy resolves, a decannulation may be proposed. Deglutition is a complex act that involves the coordinated interaction of several structures of the aerodigestive tract. Fiber-optic endoscopy and videofluoroscopy are two useful and complementary tools for the evaluation of patients with swallowing disorders. When managing these patients, a thorough knowledge on laryngeal and swallowing physiology, and on the different therapeutic alternatives, is required. Although it is not uncommon that swallowing disorders coexist in tracheostomized patients, decannulation is not synonymous with evaluationof deglutition. A patient could be a candidate for decannulation having a swallowing disorder, or a trachostomized patient could swallow adequately. Knowing and understanding these concepts will lead to a more efficient management, and helps to clarify the communication between the intensivist and the otorhinolaryngologist. Ideally, a multidisciplinary team should be formed to evaluate and manage these patients.